1989
DOI: 10.1099/0022-1317-70-6-1561
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bovine Herpesvirus Type 1 Glycoproteins gI and gIII on Herpesvirus Infections

Abstract: SUMMARYWe expressed the bovine herpesvirus type 1 (BHV-1) glycoproteins, gI and gIII, in bovine cells using a bovine papillomavirus vector. The proteins expressed by these cells had the same Mr as the native BHV-1 proteins and monoclonal antibodies detected no differences in their antigenic structure. Cells expressing gI were infected with either BHV-1 or herpes simplex virus type 1 (HSV-1). The number of plaques in gI-expressing cells was similar to that seen with normal fibroblasts infected with BHV-1 or HSV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…It is particularly noteworthy that the fusogenic activity associated with gI expression, observed previously in transfected LMTK-cells (Fitzpatrick et al, 1988), was reproducible in transfected MDBK cells. This result suggests that gI-associated cell fusion is not species-specific, as recently suggested (Chase et al, 1989) and that it is not dependent on the abnormal intracellular distribution of an atypical recombinant molecule. The lack of cell fusion in gI-expressing, transfected bovine fibroblasts noted by Chase et al (1989) may be due to a number of factors, including cell-specific differences between MDBK cells and bovine fibroblasts, use of an inducible rather than a constitutive expression system, different cell culture conditions during selection and cloning procedures, and/or quantitative differences in gI expression levels.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…It is particularly noteworthy that the fusogenic activity associated with gI expression, observed previously in transfected LMTK-cells (Fitzpatrick et al, 1988), was reproducible in transfected MDBK cells. This result suggests that gI-associated cell fusion is not species-specific, as recently suggested (Chase et al, 1989) and that it is not dependent on the abnormal intracellular distribution of an atypical recombinant molecule. The lack of cell fusion in gI-expressing, transfected bovine fibroblasts noted by Chase et al (1989) may be due to a number of factors, including cell-specific differences between MDBK cells and bovine fibroblasts, use of an inducible rather than a constitutive expression system, different cell culture conditions during selection and cloning procedures, and/or quantitative differences in gI expression levels.…”
supporting
confidence: 59%
“…Conclusions regarding the biological relevance of this phenomenon were circumspect due to the unusual features of expression of gI in transfected LMTK-cells, which were pronounced perinuclear accumulation of recombinant gI, altered N-linked glycosylation of the amino-terminal cleavage fragment of recombinant gI, and complete proteolytic cleavage of recombinant gI (Fitzpatrick et al, 1988). Recently, others have failed to detect fusion of transfected bovine fibroblasts expressing gI and have suggested that gI-associated cell fusion may be species-specific (Chase et al, 1989).…”
mentioning
confidence: 99%
“…It has three major envelope glycoproteins; gB, gC, and gD, which are involved in attachment (gB, gC and gD) and penetration (gB and gD) of BHV-1 into host cells (37, 41). Although all these glycoproteins are effective immunogens and can induce significant protection from virulent field challenge (4, 12, 20, 56, 61), gD is considered a major target for neutralizing antibodies and cytotoxic T lymphocytes (4, 15, 44, 56, 57). Several studies have been conducted to use gD in DNA or subunit vaccines to induce protective immune responses against BHV-1 on mucosal surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…However, the specific glycoprotein-based ELISA has not been commercially available for rapid detection of seroconversion by vectored vaccines against ILTV. Therefore, in the present study, we developed rapid diagnostic ELISAs by using ILTV gB, gC, and gD (B-, C-, and D-ELISAs, respectively) as antigens, since these glycoproteins can induce humoral and cellmediated immune responses against ILTV and other herpesviruses (7,(11)(12)(13)(14). Each glycoprotein was eukaryotically expressed in insect cells.…”
mentioning
confidence: 99%